Cognitive and Affective Determinants of Financial Health: The Role of Emotion Regulation and Islamic Financial Literacy - Jihan Nabila Zahara; Afitria Rizkiana; Cindy Dewi Yani; Wahyudi Setiawan; Isna Fidiyaningsing (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
Purpose: This study aims to analyze the influence of emotion regulation and Islamic financial literacy on the financial health of employees working in Islamic financial institutions in Ponorogo. Method: This study employed a quantitative explanatory approach. Data were collected through a Likert-scale questionnaire distributed to 110 respondents selected using purposive sampling. The data were analyzed using multiple linear regression with SPSS version 26 to empirically examine the relationship between the variables. Results: The findings reveal that emotion regulation has a positive and significant effect on financial health, with a significance value of 0.000 < 0.05. This indicates that individuals with better emotional control tend to have healthier financial conditions. Islamic financial literacy also has a positive and significant effect on financial health, with a significance value of 0.005 < 0.05. This suggests that a stronger understanding of Islamic financial principles contributes to better personal financial management. Implication: Theoretically, this study contributes to the development of Islamic financial behavior literature by adopting the Cognitive–Affective Theory of Behavior as the main analytical framework. This framework integrates cognitive and affective dimensions in explaining individual financial health. Originality: The originality of this study lies in its integrative model of financial behavior based on Islamic values, which positions emotion regulation and Islamic financial literacy as key determinants of the financial health of employees in Islamic financial institutions.